Introduction to disciplined agile delivery a small agile team's journey from Scrum to DevOps - Lines, Mark 1964-; Ambler, Scott W. 1966- (Project Management Institute, Inc., 2020)
How does a small development team in an established enterprise apply Disciplined Agile (DA) strategies to successfully improve their agility and provide real value to their stakeholders? Find out how in Introduction to Disciplined Agile Delivery-- Second Edition. This guide to Disciplined Agile Delivery (DAD) provides the foundation from which to scale agile and lean software development strategies, enabling teams to succeed in the unique situations they face--remembering that context counts. Starting with a Scrum-based approach, we'll show you how the team learns from their experiences and evolves into a lean life cycle, then to a continuous delivery life cycle within a DevOps environment. We begin with an overview of DAD and work through a case study that describes a team's learnings through several releases of a mission-critical solution. You'll find out how DAD: • Gives you the flexibility to use various approaches while covering gaps not addressed by mainstream agile practices. • Describes proven strategies that show how programming, design, testing, architecture, analysis, deployment, and many more aspects of solution delivery fit together in a streamlined whole. • Shows you how to turn the agile software development dial all the way up! Mark Lines and Scott Ambler Mark Lines and Scott W. Ambler are cocreators of PMI Disciplined Agile and authors of several books about agile approaches. They have decades of experience implementing agile and lean approaches at organizations around the world and are both sought-after keynote speakers.
Includes bibliographical references and index. - Online resource; title from title details screen (O'Reilly, viewed February 15, 2022)
Keywords: Agile software development; Méthodes agiles (Développement de logiciels)